The epidemiology and disease burden of rotavirus infection in the Salento peninsula, Italy - Grassi, Tiziana; De Donno, Antonella; Guido, Marcello; Gabutti, Giovanni; Collaborative Group for the Surveillance of Rotavirus Infection (The Turkish Journal of Pediatrics, 2008)
The aim of this study was to delineate the epidemiology of rotavirus gastroenteritis in the Salento peninsula, Italy. The study lasted a year and included the gathering of data on hospitalizations for enteritis caused by rotaviruses in the pediatric wards of seven hospitals in the Province of Lecce. During 2004, 7,938 children were hospitalized; 973 of them had gastroenteric symptoms and 202 were positive for rotavirus. The percentage of admissions to hospital was high in autumn and at the beginning of spring. The highest incidence of the disease was observed in children aged between 1 and 2 years, especially males. The morbidity of diarrhea caused by rotavirus followed a seasonal pattern and a distribution in terms of age group and sex that were in line with what has been seen in other geographical areas. In conclusion, on the basis of the data gathered in this study, the cases of acute gastroenteritis seem to represent an important cause of hospitalization in the Salento peninsula.